DAMPAK MEDIA LEAFBLOG SCAN BARCODE TERHADAP KESADARAN PEMELIHARAAN DAN KEBERSIHAN GIGI MAHASISWA ORTHODONTI DI POLTEKKES TANJUNGKARANG - Desi Andriyani; Lies elina Prasetiowati; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Maintenance of dental hygiene in orthodontic users needs to be given special attention, because food debris is more easily attached and triggers plaque buildup. Knowledge is very influential on oral hygiene because understanding the causes and consequences of oral hygiene can increase action to maintain oral hygiene. The research method used is quantitative method with experimental method by conducting pre-test and post-test on respondents. The sampling technique used a total of 56 respondents. The data collection instrument uses a questionnaire in the form of checklist data and direct OHI-S checking. The results of the data analysis test (Wilcoxon) show that there is a difference in knowledge about maintaining dental hygiene between before and after getting counseling using Leafblog Scan Barcode media with a p-value obtained on the knowledge variable of 0.000,<0.005, while on the dental hygiene status variable (OHI-S) there is a difference before and after getting counseling with a p-value of 0.000 <0.005.